Síntese e caracterização fotofísica de complexos polipiridínicos de Re(I) baseados no ligante 1,2-bis(4-piridil)etano - Sousa, Sinval Fernandes de (2014)
In this work, the spectroscopycal and photophysical properties of Re(I) complexes based on 1,2-bis(4-pyridyl)ethane (bpa) with the polypyridyl ligands 1,10-phenanthroline (phen), pyrazine[2,3-f][1,10]phenanatroline (dpq) and dipyrido[3,2-a:2 ,3 -c]phenazine (dppz). The complexes, fac-[Re(CO)3(NN)(bpa)]PF6, were characterized by hydrogen nuclear magnetic resonance (1H NMR) and the experimental UV-Vis spectra were compared to theoretical simulations obtained by time-dependent density function theory (TD-DFT). The photophysical properties of the complexes are dependent on the polypyridyl ligands. The emission quantum yield to the complex fac-[Re(CO)3(phen)(bpa)]PF6 is 0.11 ( = 970 ns) while for fac-[Re(CO)3(dpq)(bpa)]PF6 and fac-[Re(CO)3(dppz)(bpa)]PF6 are 0.05 ( = 375 ns) and 10-4, respectively. The emissive states of fac-[Re(CO)3(phen)(bpa)]PF6 and fac-[Re(CO)3(dpq)(bpa)]PF6 were investigated by quenching experiments in the presence of hydroquinone in acetonitrile and acetonitrile/water (1:1). The quenching processes can be fitted to the Stern-Volmer model, with quenching rate constants of (2.9 ± 0.1)x109 and (4,6 ± 0,1)x109 L mol-1 s-1 for fac-[Re(CO)3(phen)(bpa)]PF6 and (2.6 ± 0.1)x109 and (4,2 ± 0,1)x109 L mol-1 s-1 for fac-[Re(CO)3(dpq)(bpa)]PF6 , in CH3CN and in 1:1 CH3CN/H2O, respectively (T = 298K). The luminescence properties were also investigated in poly(methyl methacrylate) (PMMA) films and in glassy medium (ethanol:methanol, 4:1) at 77 K. For the complexes fac-[Re(CO)3(phen)(bpa)]PF6 and fac-[Re(CO)3(dpq)(bpa)]PF6, one can observed broad bands in both media. The emission maxima are blue shifted in relation to the one observed in acetonitrile at 298 K. This behavior was not observed for fac-[Re(CO)3(dppz)(bpa)]PF6 that exhibited a structured emission band in glassy medium. The absence of the so-called rigidochromic effect, as well as the similarity to the free dppz ligand emission profile indicate that the 3ILdppz is the low lying emissive state in fac-[Re(CO)3(dppz)(bpa)]PF6. For fac-[Re(CO)3(phen)(bpa)]PF6 and fac-[Re(CO)3(dpq)(bpa)]PF6 the behaviors are consistent with 3MLCTReNN emitters.